A protocol of a cross-sectional study evaluating an online tool for early career peer reviewers assessing reports of randomised controlled trials - Chauvin, Anthony (BMJ Open, 2017)
INTRODUCTION: Systematic reviews evaluating the impact of interventions to improve the quality of peer review for biomedical publications highlighted that interventions were limited and have little impact. This study aims to compare the accuracy of early career peer reviewers who use an innovative online tool to the usual peer reviewer process in evaluating the completeness of reporting and switched primary outcomes in completed reports. METHODS AND ANALYSIS: This is a cross-sectional study of individual two-arm parallel-group randomised controlled trials (RCTs) published in the BioMed Central series medical journals, BMJ, BMJ Open and Annals of Emergency Medicine and indexed with the publication type ‘Randomised Controlled Trial’. First, we will develop an online tool and training module based (a) on the Consolidated Standards of Reporting Trials (CONSORT) 2010 checklist and the Explanation and Elaboration document that would be dedicated to junior peer reviewers for assessing the completeness of reporting of key items and (b) the Centre for Evidence-Based Medicine Outcome Monitoring Project process used to identify switched outcomes in completed reports of the primary results of RCTs when initially submitted. Then, we will compare the performance of early career peer reviewers who use the online tool to the usual peer review process in identifying inadequate reporting and switched outcomes in completed reports of RCTs at initial journal submission. The primary outcome will be the mean number of items accurately classified per manuscript. The secondary outcomes will be the mean number of items accurately classified per manuscript for the CONSORT items and the sensitivity, specificity and likelihood ratio to detect the item as adequately reported and to identify a switch in outcomes. We aim to include 120 RCTs and 120 early career peer reviewers. ETHICS AND DISSEMINATION: The research protocol was approved by the ethics committee of the INSERM Institutional Review Board (21 January 2016). The study is based on voluntary participation and informed written consent. TRIAL REGISTRATION NUMBER: NCT03119376.